Psychological depression among sixth grade students in the first Rusafa Education (Journal of the College of Basic Education, 2025)
The current research aims to identify the level of psychological depression among sixth-grade students. To achieve this goal, the researcher adapted the Al-Huwaig Psychological Depression Scale, which consists of 52 paragraphs in its original version. After that, the paragraphs were analyzed through the two extreme groups, and the relationship of the paragraph to the total score of the scale, where 12 paragraphs were dropped, so the scale in its final form consisted of 40 paragraphs. This scale achieved validity represented by apparent validity, construct validity, and differences between groups, and its reliability reached 0.86 using Cronbach's alpha method. The research sample consisted of 200 male and female students, distributed according to gender (males - females), and both specializations (scientific - literary). After using appropriate statistical methods, the results showed the following: There are statistically significant differences between males and females in the degree of psychological depression. There are no statistically significant differences between the degree of psychological depression according to scientific and literary specialization. In light of the achieved results, the researcher recommended a number of recommendations and suggestions.